Application of Artificial Immune Algorithm (AIA) in solving engineering problems - Lee Wee Leong (2023)
The title for this project is 'Application of Artificial Immune Algorithm (AIA) in Solving Engineering Problems'. The outline of this project design two Graphical User Interfaces (GUI) that can solve two engineering problems based on Artificial Immune Algorithm.